Assessing social differences in overweight among 15- to 16-year-old ethnic Norwegians from Oslo by register data and adolescent self-reported measures of socio-economic status - Lien, N; Kumar, B.N; Holmboe-Ottesen, G; Klepp, K.I; Wandel, M (International Journal of Obesity, 2007)
Objective: To determine to what extent self-reported and objective data on socio-economic status (SES) are associated with overweight/obesity among 15 to 16-year-old ethnic Norwegians. Design: A cross-sectional questionnaire study on health and health-related behaviors. Subjects: All school children aged 15-16 years old in 2000 and 2001 in Oslo, Norway. Response rate 88% (n=7343). This article is based on the data from the 5498 ethnic Norwegians. Measurements: Self-reported height and weight were used to measure overweight (including obesity) as defined by the International Obesity Task Force cutoffs at the nearest half-year intervals. SES was determined by register data from Statistics Norway on residential area, parental education and income and by adolescent self-reported measures on parental occupation and adolescents' educational plans. Results: The prevalence of overweight/obesity was low, but higher among boys (11%) than among girls (6%). Parental education (four levels) showed the clearest inverse gradients with overweight/obesity (boys: 18, 13, 10 and 7%; girls: 11, 6, 6 and 4%). Parental education remained significantly associated with overweight/obesity when adding occupation and income to the model for the boys, whereas there were no significant associations in the final model for the girls. Overweight/obesity was associated with a lower odds ratio of planning for higher education (college/university) among boys only. Conclusion: For the boys, parental education was most strongly associated with overweight/obesity, and the association between overweight/obesity and educational plans appears to imply downward social mobility. The relationships between the various SES measures and overweight/obesity appeared more interrelated for the girls.